Stability analysis, flexible control and optimal operation of microgrid - Li, Yong; Zhang, Mingmin; Cao, Yijia (Springer, 2023)
This book intends to report the new results of the microgrid in stability analysis, flexible control and optimal operation. The oscillatory stability issue of DC microgrid is explored and further solved. Flexible and stable voltage & frequency control of microgrid is put forward considering the distributed generations or distributed energy storages. The optimal operation of multi-energy is researched in view of economic efficiency and low-carbon development. The results of this book are original from authors who carry out the related research together for a long time, which is a comprehensive summary for authors’ latest research results. The book is likely to be of interest to university researchers, electrical engineers and graduate students in power systems, power electronics, renewable energy and microgrid